A disulfide-based linker for thiol–norbornene conjugation: formation and cleavage of hydrogels by the use of light. Issue 9 (20th January 2022) - Lunzer, Markus; Maryasin, Boris; Zandrini, Tommaso; Baudis, Stefan; Ovsianikov, Aleksandr; Liska, Robert
Abstract : A photolinker for formation of disulfide-crosslinked hydrogels via light-triggered thiol–ene conjugation has been developed. Hydrogels can be patterned via two-photon cleavage of disulfide-linkages in the presence of a two-photon active compound. Abstract : Photolabile groups are the key components of photo-responsive polymers, dynamically tunable materials with multiple applications in materials and life sciences. They usually consist of a chromophore and a labile bond and are inherently light sensitive. An exception are disulfides, simple reversible linkages, which become photocleavable upon addition of a photoinitiator. Despite their practical features, disulfides are rarely utilized due to their impractical formation. Here, we report a disulfide-based linker series bearing norbornene terminals for facile crosslinking of thiol-functionalized macromers via light-triggered thiol–ene conjugation (TEC). Besides finding a highly reactive lead compound, we also identify an unexpected TEC-retardation, strongly dependent on the molecular linker structure and affecting hydrogel stability. Finally, we present a useful method for localized disulfide cleavage by two-photon irradiation permitting micropatterning of disulfide-crosslinked networks.